Bedside Blood Transfusion - What Nurses Know and Perform: A Cross-Sectional Study from A Tertiary-Level Cancer Hospital in Rural Kerala - Irene Elizabeth Jogi; Nithya Mohanan; Nisanth Menon Nedungalaparambil (Elsevier, 2021)
Objective: Nursing professionals are expected to have updated knowledge of clinical blood transfusion guidelines while catering to cancer patients requiring bedside transfusions. Methods: A cross-sectional study was conducted to evaluate the knowledge and current practice of nurses at a tertiary-level cancer hospital in rural Kerala using a pretested self-administered structured 20-item questionnaire, and results were analyzed. Results: Among 246 nurses who participated, a response rate of 93.08% (n = 229) was obtained. Mean scores of 4.64 ± 1.20 out of eight for knowledge-based questions (58.00%) and 6.16 ± 1.49 out of 12 for practical aspects (51.33%) were obtained among respondents. Whereas overall scores were fair (84.28% and 65.94% nurses scoring ≥50% in knowledge-based and practice-based questions, respectively), we noticed poor knowledge-level scores for the key aspects such as time taken for cross-matching, cross-match test taking least time, storage temperature, and mandatory transfusion-transmitted infection tests before initiating transfusion. Poor scores were also noted for key clinical practices relating to warming of blood products, posttransfusion patient monitoring, rate of nonemergency blood transfusions, administration of premedications, and disposal of blood bags among the respondents. Data also revealed that there was a lack of adherence to a uniform cannula size for routine blood transfusion among nurses. Work experience or qualification had no significant relation to the nurses' scores for knowledge or practice-based questions. Conclusions: Overall, a fair amount of theoretical and practical knowledge about bedside transfusion practices were observed among nurses with some inconsistencies not related to qualification or work experience. This illuminates inherent lacunae in the existing training system and merits urgent redressal.